Premier advisory services for VIP acquirers - Liu, Qi; Sun, Xian; Wu, Hong (Journal of Corporate Finance, 2019)
We model an investment bank's choice of resource allocation by the probability of acquirers' mergers and acquisitions frequency in the future to theoretically link the role of investment banks to the acquirer returns. Our model predicts the heterogeneity in the quality of advisory services provided by the same investment bank that leads to the heterogeneity in acquirer returns. Such heterogeneity declines as the likelihood of an industry merger wave rises. Controlling for investment bank fixed effects, acquirer fixed effects and potential self-selection bias, we find empirical evidence supporting our hypotheses.